2019
DOI: 10.1021/acs.analchem.9b03720
|View full text |Cite
|
Sign up to set email alerts
|

Retention Time and Optimal Collision Energy Advance Structural Annotation Relied on LC–MS/MS: An Application in Metabolite Identification of an Antidementia Agent Namely Echinacoside

Abstract: The structural annotation of metabolites now relies heavily on HR-MS/MS information, resulting in ambiguous identities in most cases. More auxiliary evidence is therefore desired to achieve confirmative identification. Herein, we made an attempt to involve retention time (t R ) along with optimal collision energy (OCE) as the additionally structural clues, and the applicability validation was conducted via confidence-enhanced metabolite characterization of echinacoside, an antidementia drug candidate within cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 30 publications
0
44
0
Order By: Relevance
“…Because of the insufficient metabolic stability, the bioavailability of both VB and ECH has been demonstrated, as expected, to be quite low, 194,195 merely 0.83% for ECH and 0.12% for VB 196 . As a consequence, many concerns have paid onto the metabolism profiles of these individual components, in particular VB, 197–202 ECH, 190,202–204 poliumoside, 205,206 isoacteoside, 199 and 2′‐acetylacteoside 199 . All the studies concluded that deglycosylation, hydroxytyrosol clavage, decaffeoylation, deacetylation, reduction, acetylation, glucuronidation, and sulfation were primarily responsible for the low bioavailability as well as for the generation of most metabolites.…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 90%
See 2 more Smart Citations
“…Because of the insufficient metabolic stability, the bioavailability of both VB and ECH has been demonstrated, as expected, to be quite low, 194,195 merely 0.83% for ECH and 0.12% for VB 196 . As a consequence, many concerns have paid onto the metabolism profiles of these individual components, in particular VB, 197–202 ECH, 190,202–204 poliumoside, 205,206 isoacteoside, 199 and 2′‐acetylacteoside 199 . All the studies concluded that deglycosylation, hydroxytyrosol clavage, decaffeoylation, deacetylation, reduction, acetylation, glucuronidation, and sulfation were primarily responsible for the low bioavailability as well as for the generation of most metabolites.…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 90%
“…Judging from the chemical structure of a given PhG, theoretically, hydrolytic enzymes are able to dissociate both the ester moieties and ether‐type glucosidic bonds between sugar residues as well as between phenethyl aglycone and glucosyl residue, resulting in the extensive occurrences of hydrolyzed products. These hydrolyzed products such as caffeic acid, tyrosol, and hydroxytyrosol, usually exist as the theoretical intermediates because they usually bear more than one labile site, for example, hydroxyl and carboxyl groups to receive subsequent glucuronidation and/or sulfation 190 . So far, a set of publications are available concerning the metabolism of PhGs in vitro and in vivo when administrating single component or the extract.…”
Section: Pharmacokinetics and Metabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, acyl-migration and acetylization of verbascoside (M17) produced isoverbascoside (M18) and acetyl-verbascoside (M19). 213 Three metabolites of forsythiaside A (200 mg/kg, po) were identified in rats, with 42 in urine, 22 in plasma, and 15 in feces. 214 In general, forsythiaside A was mainly methylated, dimethylated, sulfated, glucuronidated, diglucuronidated, and cysteine conjugated.…”
Section: Metabolites In Vivomentioning
confidence: 98%
“…Afterward, the two intermediates received sulfonation, glucuronidation, methylation, oxidation, reduction, and/or hydrogenation to finally generate M1−M16. In addition, acyl‐migration and acetylization of verbascoside (M17) produced isoverbascoside (M18) and acetyl‐verbascoside (M19) 213 . Three metabolites of forsythiaside A (200 mg/kg, po) were identified in rats, with 42 in urine, 22 in plasma, and 15 in feces 214 .…”
Section: Pharmacokinetics Of Phgsmentioning
confidence: 99%